Aversive anticipations modulate electrocortical correlates of decision-making and reward reversal learning, but not behavioral performance - Bublatzky, Florian; Schellhaas, Sabine; Paret, Christian (Frontiers in Behavioral Neuroscience, 2022)
Predicting the consequences of one’s own decisions is crucial for organizing future behavior. However, when reward contingencies vary frequently, flexible adaptation of decisions is likely to depend on the situation. We examined the effects of an instructed threat context on choice behavior (i.e., reversal learning) and its electrocortical correlates. In a probabilistic decision-making task, 30 participants had to choose between two options that were either contingent with monetary gains or losses. Reward contingencies were reversed after reaching a probabilistic threshold. Decision making and reversal learning was examined with two contextual background colors, which were instructed as signals for threat-of-shock or safety. Self-report data confirmed the threat context as more unpleasant, arousing, and threatening relative to safety condition. However, against our expectations, behavioral performance was comparable during the threat and safety conditions (i.e., errors-to-criterion, number of reversal, error rates, and choice times). Regarding electrocortical activity, feedback processing changed throughout the visual processing stream. The feedback-related negativity (FRN) reflected expectancy-driven processing (unexpected vs. congruent losses and gains), and the threat-selective P3 component revealed nonspecific discrimination of gains versus losses. Finally, the late positive potentials (LPP) showed strongly valence-specific processing (unexpected and congruent losses vs. gains). Thus, regardless of contextual threat, early and late cortical activity reflects an attentional shift from expectation- to outcome-based feedback processing. Findings are discussed in terms of reward, threat, and reversal learning mechanisms with implications for emotion regulation and anxiety disorders.